Means and Ends in Cross Border Marketing : Ethical Dimensions of Promotional Activities of The Online Casino - Kathuria, Kapil; Dhaulta, Nipun (Prabandhan: Indian Journal of Management, 2018)
The case discussed the marketing activities of The Online Casino, which is using publicity to promote its brand while bypassing the restrictions that have been placed on advertising of gambling in many countries. The publicity events and acts are debatable from an ethical point of view in addition to the services offered being ethically debatable itself. That the gambling opportunity is being offered online raises issues of ethics and breaches legal provisions in countries where gambling is illegal. To the extent that laws reflect the culture of country/region, the case examined ethical issues arising from cross cultural marketing.